New insights towards mesoporous silica nanoparticles as a technological platform for chemotherapeutic drugs delivery - Sábio, Rafael M.; Meneguin, Andréia B.; Ribeiro, Taís C. [UNESP]; Silva, Robson R.; Chorilli, Marlus [UNESP] (Elsevier, 2019)
Mesoporous silica nanoparticles (MSNs)displays interesting properties for biomedical applications such as high chemical stability, large surface area and tunable pores diameters and volumes, allowing the incorporation of large amounts of drugs, protecting them from deactivation and degradation processes acting as an excellent nanoplatform for drug delivery. However, the functional MSNs do not present the ability to transport the therapeutics without any leakage until reach the targeted cells causing side effects. On the other hand, the hydroxyls groups available on MSNs surface allows the conjugation of specific molecules which can binds to the overexpressed Enhanced Growth Factor Receptor (EGFR)in many tumors, representing a potential strategy for the cancer treatment. Beyond that, the targeting molecules conjugate onto mesoporous surface increase its cell internalization and act as gatekeepers blocking the mesopores controlling the drug release. In this context, multifunctional MSNs emerge as stimuli-responsive controlled drug delivery systems (CDDS)to overcome drawbacks as low internalization, premature release before to reach the region of interest, several side effects and low effectiveness of the current treatments. This review presents an overview of MSNs fabrication methods and its properties that affects drug delivery as well as stimuli-responsive CDDS for cancer treatment.
Keywords: Cancer; Chemotherapy drugs; Drug delivery; Mesoporous silica nanoparticles; Stimuli-responsive nanoplatforms